Cup is an eIF4E binding protein required for both the translational repression of oskar and the recruitment of Barentsz. - Wilhelm, J.E.; Hilton, M.; Amos, Q.; Henzel, W.J. (Journal of Cell Biology, 2003)
In Drosophila oocytes, precise localization of the posterior determinant, Oskar, is required for posterior patterning. This precision is accomplished by a localization-dependent translational control mechanism that ensures translation of only correctly localized oskar transcripts. Although progress has been made in identifying localization factors and translational repressors of oskar, none of the known components of the oskar complex is required for both processes. Here, we report the identification of Cup as a novel component of the oskar RNP complex. cup is required for oskar mRNA localization and is necessary to recruit the plus end-directed microtubule transport factor Barentsz to the complex. Surprisingly, Cup is also required to repress the translation of oskar. Furthermore, eukaryotic initiation factor 4E (eIF4E) is localized within the oocyte in a cup-dependent manner and binds directly to Cup in vitro. Thus, Cup is a translational repressor of oskar that is required to assemble the oskar mRNA localization machinery. We propose that Cup coordinates localization with translation.